1966
DOI: 10.3402/tellusa.v18i2-3.9390
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric circulation studies based on natural and artificial radioactive tracer elements

Abstract: The nature of large scale stratospheric circulation is studied using the cosmic ray produced isotopes Par, Be", Sa6 and Nas2 as tracers. Supplementary information obtained from observations of the distribution of the bomb-produced Na** and radongenic Pbp10 is taken into account. The activities of these tracer elements have been measured in the stratospheric air, up to altitudes of 20 km, during 1960-64. Data are fairly extensive for studying the characteristics of the mean circulation in the stratosphere as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 6 publications
3
51
0
Order By: Relevance
“…However, few studies have reported beryllium measurements higher up in the stratosphere. Our simulated values of Be-7 concentration match quite well the range of measurements done at 20 km over the 脗2 yr period August 1963脕April 1965 with low solar activity (F 脗400 to 600 MV; Usoskin et al, 2011), compiled by Bhandari et al (1966). The simulated values are rather in the upper part of the range, except in sub-tropical latitudes (25脕358N) where they are lower by 脗15%.…”
Section: Simulated Beryllium Concentrationssupporting
confidence: 71%
See 3 more Smart Citations
“…However, few studies have reported beryllium measurements higher up in the stratosphere. Our simulated values of Be-7 concentration match quite well the range of measurements done at 20 km over the 脗2 yr period August 1963脕April 1965 with low solar activity (F 脗400 to 600 MV; Usoskin et al, 2011), compiled by Bhandari et al (1966). The simulated values are rather in the upper part of the range, except in sub-tropical latitudes (25脕358N) where they are lower by 脗15%.…”
Section: Simulated Beryllium Concentrationssupporting
confidence: 71%
“…As a result, beryllium concentrations in the troposphere are one to two orders of magnitude lower than in the stratosphere (e.g. Bhandari et al, 1966;McHargue and Damon, 1991). This makes beryllium concentrations a potential tracer of stratospheric air inputs into the troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first consistent model was developed by D. Lal et al (Bhandari et al 1966;Lal and Peters 1967;Lal and Suess 1968), using an empirical approach based on fitting simplified model calculations to measurements of the isotope concentrations and "star" (inelastic nuclear collisions) formations in the atmosphere. Next was an analytical model by O'Brien (1979), who solved the problem of the GCR-induced cascade in the atmosphere using an analytical stationary approximation in the form of the Boltzmann equation.…”
Section: Productionmentioning
confidence: 99%